(untitled) (Shahroud Journal of Medical Sciences, 2019)
Background: Today, health care market has become a competitive market. Various factors affect the care of the hospital and the choice of hospital by patients. The present study aimed to investigate the effective factors on patients' preferences based on the mixing factors of marketing services in hospital selection. Methods: This descriptive-analytic study was performed on 300 patients referred to educational hospitals in Iran in 2018. The instrument used was a researcher-made questionnaire include two sections (demographic and Patients' Preferences questionnaire). Data was analyzed using descriptive and analytical. Results: Among the 7 components, the highest and the lowest mean and standard deviation were related to staff (1.03 ± 3.89) and location (1.10 ± 2.96), respectively. The index value of the RMSEA for the compiled model it is equal to 0.059, comparative fit index (CFI) is 0.837 and the IFI index is 0.839. Employee component with coefficient of 1.00 and price component with coefficient of 0.72 had the highest and the least effect. Conclusions: Staff and physicians and hospital space have the greatest role in attracting patients. Therefore, it is expected that the hospital management will make the essential planning, and by intervening in the process of work of physicians and staff. Key words: Patient preferences, mixed Marketing, marketing of health services, Hospital.